Novel drug compounds against neospora caninum and toxoplasma gondill in vitro. - Jitbanjong Wiengcharoen. (2014)
Neospora caninum has recently been identified as an important cause of abortion in cattle worldwide. This parasite is closely related to Toxoplasma gondii. To identify the drug compounds for potential use against both parasites in vitro, nine novel drug compounds were incubated with either parasite on microtiter plate. The number of extracellular tachyzoites and the quantities of Vero cells left in the wells after incubating with those nine drugs were compared to the conventional drug control, a combination of sulfadiazine 25 μg/ml and pyrimethamine 0.1 μg/ml. The most effective drugs against both N. caninum and T. gondii in this study were trifluralin analogues.